2010
DOI: 10.1111/j.1471-4159.2009.06496.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia protects neuronal cells from human prion protein fragment‐induced apoptosis

Abstract: J. Neurochem. (2010) 112, 715–722. Abstract Prion diseases are neurodegenerative disorders characterized by the accumulation of an abnormal isoform of the prion protein PrPSc. Human prion protein fragment, PrP (106–126) (prion protein peptide 106–126), may contain most of the pathological features associated with PrPSc. Hypoxic conditions elicit cellular responses adaptively designed to improve cell survival and have an important role in the process of cell survival. We investigate the effects of hypoxia on Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…32 In addition, the PrP Sc protein or PrP (106-126) induces neuronal cell death by increasing p53, p-ERK and p-p38 protein levels and decreasing bcl-2 protein levels. 33 Hachiya et al showed that transgenic mice harboring a high copy number of wild-type mouse PrP C developed a spontaneous neurological dysfunction, probably due to mitochondria-mediated neuronal apoptosis in aged transgenic mice overexpressing wild-type PrP C . The aged mice exhibited an aberrant mitochondrial localization of PrP C concomitant with decreased manganese superoxide dismutase activity, cytochrome c release, caspase-3 activation and DNA fragmentation, most predominantly in hippocampal neuronal cells.…”
Section: The Role Of Cellular Prion Protein In Cell Apoptosismentioning
confidence: 99%
“…32 In addition, the PrP Sc protein or PrP (106-126) induces neuronal cell death by increasing p53, p-ERK and p-p38 protein levels and decreasing bcl-2 protein levels. 33 Hachiya et al showed that transgenic mice harboring a high copy number of wild-type mouse PrP C developed a spontaneous neurological dysfunction, probably due to mitochondria-mediated neuronal apoptosis in aged transgenic mice overexpressing wild-type PrP C . The aged mice exhibited an aberrant mitochondrial localization of PrP C concomitant with decreased manganese superoxide dismutase activity, cytochrome c release, caspase-3 activation and DNA fragmentation, most predominantly in hippocampal neuronal cells.…”
Section: The Role Of Cellular Prion Protein In Cell Apoptosismentioning
confidence: 99%
“…cell lines were lysed in a lysis buffer (25 mM HePeS; pH 7.4, 100 mM nacl, 1 mM edTa, 5 mM Mgcl 2 , 0.1 mM dTT and protease inhibitor mixture). Proteins were electrophoretically resolved on an 8-15% SdS gel, and immunoblotting was performed as previously described (19). equal amounts of protein lysates were resolved on an 8-15% SdS-polyacrylamide gel and electrophoretically transferred to a nitrocellulose membrane.…”
Section: Terminal Deoxynucleotidyl Transferase Dutp Nick End Labelingmentioning
confidence: 99%
“…Although the mechanisms of PrPSc neurotoxicity are yet unclear, recent studies support the hypothesis that PrPSc induces neuronal cell death and activates caspase-3 through the p38-JNK mitogen-activated protein kinase (MAPK) pathway (2,11,12). Seo et al studying PrP peptide 106-126 [PrP(106-126)]-treated SH-SY5Y cells, have shown that PrP(106-126)-induced neurotoxicity is decreased by repression of p38 MAPK activation with exposure to the SIRT1 activator, resveratrol (13).…”
Section: Introductionmentioning
confidence: 96%